2018
DOI: 10.1016/j.scitotenv.2018.06.363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prescribed burning for pasture reclamation on soil chemical properties in subalpine shrublands of the Central Pyrenees (NE-Spain)

Abstract: The abandonment of the traditional pastoral activities in the subalpine grasslands of the Central Pyrenees (NE-Spain) has resulted in shrub encroachment processes that are dominated by species such as the Echinospartum horridum. Therefore, prescribed burning has been recently readopted in this region as a management tool to stop the spread of shrubs and recover grasslands. We aimed to assess the effect that this practice may have on soil chemical properties such as SOC, N, pH, EC, water-extractable and exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 51 publications
0
4
0
3
Order By: Relevance
“…Otherwise, EC shows a significant correlation with the main exchangeable cations (Ca 2+ and Mg 2+ ) and organic matter. Many authors have also found that pH and EC sometimes are not affected the same way after a fire (Girona-García et al, 2018c;Granged et al, 2011;Mills and Fey, 2004), while others like Muñoz-Rojas et al (2016) have found, in fact, a high correlation between them. The decrease in EC and the main exchangeable cations over time is not surprising in an environment with about 1700 mm/yr of MAP (Úbeda et al, 2005;Ulery et al, 1993) and with a recovering vegetation Table 4 Evolution of properties (0-1, 1-2 and 2-3 cm depth) for unburned and burned soils (at 0, 6 and 10 years after burning): pH, Electrical conductivity (EC) and Exchangeable cations (Ca 2+ , Mg 2+ , K + ).…”
Section: Other Soil Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, EC shows a significant correlation with the main exchangeable cations (Ca 2+ and Mg 2+ ) and organic matter. Many authors have also found that pH and EC sometimes are not affected the same way after a fire (Girona-García et al, 2018c;Granged et al, 2011;Mills and Fey, 2004), while others like Muñoz-Rojas et al (2016) have found, in fact, a high correlation between them. The decrease in EC and the main exchangeable cations over time is not surprising in an environment with about 1700 mm/yr of MAP (Úbeda et al, 2005;Ulery et al, 1993) and with a recovering vegetation Table 4 Evolution of properties (0-1, 1-2 and 2-3 cm depth) for unburned and burned soils (at 0, 6 and 10 years after burning): pH, Electrical conductivity (EC) and Exchangeable cations (Ca 2+ , Mg 2+ , K + ).…”
Section: Other Soil Parametersmentioning
confidence: 99%
“…that absorbs essential nutrients (Alcañiz et al, 2016). The incorporation of basic ash, rich in soluble ions and salts (Muñoz-Rojas et al, 2016), into the soil is likely to happen and causes these parameters to increase in the short term (Alcañiz et al, 2018;Gil et al, 2010), sometimes right after the PB (Francos et al, 2019;Girona-García et al, 2018c;Granged et al, 2011) and sometimes within the next few years (Alcañiz et al, 2016;Fontúrbel et al, 2016;Girona-García et al, 2018c). Those effects are expected to disappear in the mid-and long-term.…”
Section: Other Soil Parametersmentioning
confidence: 99%
“…2) moisture and amount of fuel loads (Neary et al, 1999); 3) weather conditions (Fernandes et al, 2013); 4) soil water content (Massman, 2012); 5) the sampled soil thickness (Badía-Villas, et al, 2014) and 6) whether the ashes were completely removed prior to sampling (Girona-García et al, 2018b).…”
Section: Contrasting Effects Of Prescribed Burning On Soc and N Stock...mentioning
confidence: 99%
“…Los suelos constituyen un recurso indispensable para la vida, siendo primordiales para nuestra sobrevivencia (CRUZ et al, 2004;RAMÍREZ;SÁNCHEZ, 2012). Sin embargo, este recurso ha estado sujeto a fuertes presiones generadas por diversas actividades, entre las que destacan los incendios forestales.…”
Section: Introductionunclassified